2020 IEEE Symposium on Security and Privacy (SP) 2020
DOI: 10.1109/sp40000.2020.00037
|View full text |Cite
|
Sign up to set email alerts
|

Path Oblivious Heap: Optimal and Practical Oblivious Priority Queue

Abstract: We propose Path Oblivious Heap, an extremely simple, practical, and optimal oblivious priority queue. Our construction also implies a practical and optimal oblivious sorting algorithm which we call Path Oblivious Sort. Not only are our algorithms asymptotically optimal, we show that their practical performance is only a small constant factor worse than insecure baselines. More specificially, assuming roughly logarithmic client private storage, Path Oblivious Heap consumes 2× to 7× more bandwidth than the ordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…However, it is to be observed that prior ( log )-work oblivious algorithms for sorting -the AKS network [2], Zigzag sort [38], and an ( log ) version of oblivious bucket sort [4] all use expanders within their construction. Sorting can be performed using an efficient oblivious priority queue that does not use expanders [42,51]; however this incurs ( log ) work to achieve a negligible in failure probability. Further, this method is not cache-efficient and is inherently sequential.…”
Section: Our Resultsmentioning
confidence: 99%
“…However, it is to be observed that prior ( log )-work oblivious algorithms for sorting -the AKS network [2], Zigzag sort [38], and an ( log ) version of oblivious bucket sort [4] all use expanders within their construction. Sorting can be performed using an efficient oblivious priority queue that does not use expanders [42,51]; however this incurs ( log ) work to achieve a negligible in failure probability. Further, this method is not cache-efficient and is inherently sequential.…”
Section: Our Resultsmentioning
confidence: 99%
“…Further, we find that perception blinding is highly effective in mitigation of manifold learning-based SCA. We also demonstrate the noise resiliency of our attack, and how oblivious RAM [42,97] can mitigate our attack, though it incurs high cost and becomes impractical in real-life usage. In summary, this thorough study makes the following contributions:…”
Section: Introductionmentioning
confidence: 91%
“…That said, oblivious RAM (ORAM) [42] conceal memory access sequences of a program by continuously shuffling data as they are accessed. We study whether a representative ORAM, PathOHeap [97], can mitigate our attack. Due to the limited space, we report the key evaluation results in Table 13.…”
Section: Mitigation Using Orammentioning
confidence: 99%
See 1 more Smart Citation
“…Neither of these works looked at the problem of sampling. In a concurrent and independent work, Shi [34] has developed a data-oblivious sampling algorithm for generating one random sample from a stream of elements. In comparison, we consider the setting where k samples need to be generated from a dataset of n elements, thereby amortising the cost of processing the dataset across multiple samples.…”
Section: Related Workmentioning
confidence: 99%